Parameters of the Transmembrane Transport of Pelophylax ridibundus in the Conditions of Thermal Reservoirs - Gurvich, A N (KnE Life Sciences, 2018)
Study of Pelophylax ridibundus skin physiological parameters in a thermal basin shows that there are seasonal differences in PD (potential difference) and ISC (active transportation parameter). Amphibians studied in the summer time in a control area showed some differences compared to specimens caught in summer time in a basin with higher temperatures (River Malaya Kushva). We may suppose that this is connected with the habitation adaptation of the population.